Meningkatkan Motivasi Belajar Melalui Penerapan Ice Breaking Pada Pembelajaran Al-Qur’an Hadist - Usmaidar, Usmaidar; Ridha, Zaifatur; Maulida, Nurleli (Wangsa : Journal of Education and Learning, 2025)
Learning the Qur’an and Hadith as the primary sources of Islamic teachings is fundamental to understanding Islamic faith (aqidah), law (shari‘ah), and morality (akhlaq). This learning process is not solely oriented toward textual mastery but also toward internalizing meanings and implementing values in daily life. However, in the context of rapid modernization, Qur’an and Hadith learning faces several challenges, including low student interest and motivation, limited use of innovative teaching methods, and exposure to inaccurate information. These issues were particularly evident among grade X students at MAS Al-Yusriah Pangkalan Susu. To address these challenges, this study implemented the Ice Breaking Method to enhance students’ learning motivation and engagement in the Qur’an and Hadith subject. The research employed Classroom Action Research (CAR) conducted in two cycles. The participants consisted of 19 grade X students, including 8 male and 11 female students. The findings indicate that the Ice Breaking Method significantly improved students’ learning motivation. Learning activity scores increased from 68.42% in the first cycle to 89.47% in the second cycle, reflecting an improvement of 21.05%. These results demonstrate that the Ice Breaking Method is effective in fostering active participation and increasing motivation in Qur’an and Hadith learning. Therefore, it is recommended that teachers adopt more creative and interactive instructional strategies to ensure that Qur’an and Hadith lessons become more engaging, meaningful, and relevant to students’ learning experiences.